Signaling from the cytoplasm to the nucleus in striatal medium-sized spiny neurons - Miriam eMatamales; Miriam eMatamales; Miriam eMatamales; Jean-Antoine eGirault; Jean-Antoine eGirault; Jean-Antoine eGirault (Frontiers Media S.A., 2011)
Striatal medium-sized spiny neurons (MSNs) receive massive glutamate inputs from the cerebral cortex and thalamus and are a major target of dopamine projections. Interaction between glutamate and dopamine signaling is crucial for the control of movement and reward-driven learning, and its alterations are implicated in several neuropsychiatric disorders including Parkinson's disease and drug addiction. Long-lasting forms of synaptic plasticity are thought to depend on transcription of gene products that alter the structure and/or function of neurons. Although multiple signal transduction pathways regulate transcription, little is known about signal transmission between the cytoplasm and the nucleus of striatal neurons and its regulation. Here we review the current knowledge of the signaling cascades that target the nucleus of MSNs, most of which are activated by cAMP and/or Ca2+. We outline the mechanisms by which signals originating at the plasma membrane and amplified in the cytoplasm are relayed to the nucleus, through the regulation of several protein kinases and phosphatases and transport through the nuclear pore. We also summarize the identified mechanisms of transcription regulation and chromatin remodeling in MSNs that appear to be important for behavioral adaptations, and discuss their relationships with epigenetic regulation.